Analysis of the 6 – 10 kV Cable Lines Faults in Vilnius City - Karaliūnas, B. (Elektronika ir Elektrotechnika, 2006)
Reasons and causes of faults and defects in 6 – 10 kV cable lines in Vilnius city and in the neighborhood regions as well as renovation possibilities in cable lines are analyzed. While expanding the construction works and renovating old buildings in Vilnius city the power cables with oil – paper insulation are being substituted by reinforced cross – linked polyethylene cables (XLPE). The present state of cable lines is analyzed as well as cable insulation technical characteristics. The imitation model of insulation of partial discharge in the micro voids is presented in the article, allowing to investigate insulation life time dependence on the intensity of operating electric field. The analysis of statistical data indicate the fact that when the number of tests on cables using high – voltage tests was reduced there appeared emergency faults in 6 – 10 kV cable networks. The faults in this network comprise 33% of the total faults, in aerial lines 28%, in cable aerial lines faults make 26%, in transformer substations there were registered 13% of faults. The most usual reasons of the registered faults and defects are the following: cable insulation ageing 51,4%, direct cable damages 18,9%, low quality materials 14,4%, errors in designs 7,4%, maintenance failures 4,6%, installation defects 1,4% and manufacturing defects 1,8%. Il. 4, bibl. 8 (in English; summaries in English, Russian and Lithuanian).